Coordinative Thinking Among Female Students of the Kindergarten Department (Journal of the College of Basic Education, 2025)
The researcher adopted the descriptive correlational approach in her research, and the research sample consisted of (400) female students from Al-Mustansiriya University, College of Basic Education / Kindergarten Department, for the stages (first, second, third, fourth) for the academic year 2024-2025. The sample was selected in a stratified random manner, and to achieve the objectives that the researcher used the following tools: The first is the Coordinative Thinking Scale, as the researcher adopted the scale according to Bartlett's theory 2001, Bartlett) , which consisted of two fields (analytical and synthetic), with (60) paragraphs. The alternatives for correcting the paragraphs were binary by giving a score of (1) to the answer that expresses the characteristic of coordinative thinking and giving (zero) to the answer that does not represent the characteristic. The researcher verified the apparent validity of the scale and the validity of the structure through discrimination, the relationship of the paragraph score to the total score, the relationship of the paragraph score to the component to which it belongs, and the internal correlation matrix. The researcher also verified the stability of the scale By the (test and retest) method, the reliability coefficient reached (0,84); and also by the Cronbach’s alpha equation, the reliability coefficient reached (0,81).